1972
DOI: 10.1083/jcb.52.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphometry of Developing Rat Liver and Its Application to Enzymic Differentiation

Abstract: Quantitative stereological methods have been adapted for the measurement of the volume of liver attributable to parenchymal, hematopoietic, and Kupffer cells and for the measurement of the relative and absolute number (per unit volume) of these cell types and the mean volume of the parenchymal cell . These morphological parameters are the main ones for interpreting the biochemical differentiation of liver . Quantitative changes in these parameters, in rat liver between the 15th day of gestation and adult life,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
1

Year Published

1975
1975
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(118 citation statements)
references
References 13 publications
8
109
1
Order By: Relevance
“…Indeed between 13 and 20 dpc in the rat pre-hepatocytes on average undergo 8 doublings and the liver expands in volume by 84-fold (Greengard et al, 1972;Vassy et al, 1988;Grisham and Thorgeirsson, 1996). Gene-inactivation studies in mice have outlined a pathway that links the growth promoting properties of septum transversum mesenchyme to regulation of the hepatocyte cell cycle, recently reviewed by Zaret (1998).…”
Section: Transcription Factors Have Important Roles In Liver Growth Amentioning
confidence: 99%
“…Indeed between 13 and 20 dpc in the rat pre-hepatocytes on average undergo 8 doublings and the liver expands in volume by 84-fold (Greengard et al, 1972;Vassy et al, 1988;Grisham and Thorgeirsson, 1996). Gene-inactivation studies in mice have outlined a pathway that links the growth promoting properties of septum transversum mesenchyme to regulation of the hepatocyte cell cycle, recently reviewed by Zaret (1998).…”
Section: Transcription Factors Have Important Roles In Liver Growth Amentioning
confidence: 99%
“…Studies in rat embryos have shown that between E13.5 and E20.5, the volume of the liver expands 84-fold, during which time the hepatoblasts undergo 8-doublings. [85][86][87] Several mechanisms have been identified through gene knockout studies in mouse embryos that are required for growth of the liver. These include protection of the fetal liver from tumor necrosis factor ␣-mediated apoptotic cell death through the nuclear factor B signaling pathway, regulation of cell proliferation by the transcription factors Xbp1 and Foxm1b, and signaling mechanisms that are mediated through the AP-1 transcription factor cJun.…”
Section: What Governs the Establishment Of Hepatic Architecture And Mmentioning
confidence: 99%
“…In liver, hepatocytes account for 70-95% of the cellular weight (lype et al, 1965;Greengard et al, 1972) and the contribution of reticulo-endothelial cell membranes to the subfractions now characterized is likely to be minor. The glucagon-stimulated adenylate cyclase activity was shown to be exclusively located in hepatocytes (Sweat & Hupka, 1971).…”
Section: Bile-canicularfacementioning
confidence: 99%